IMPLEMENTASI PELATIHAN DESAIN GRAFIS INTERAKTIF DALAM MENINGKATKAN KOMPETENSI PEMBELAJARAN SISWA SMK MUHAMMADIYAH 2 PONTIANAK - Istikoma, Istikoma; Sucipto, Sucipto; Herisandi, Desti (LPPM Universitas Bina Bangsa, 2025)
Graphic design training for Vocational High School (SMK) students is to provide the understanding and skills needed in the rapidly growing graphic design industry. SMK Muhammadiyah 2 Pontianak has two expertise, one of which is learning visual communication design. However, there are still weaknesses in creating and creating new ideas that are contemporary in nature which are considered necessary for future provisions. Graphic design training is a more appropriate way to answer the problems that occur in vocational schools which include the use of software to the basic concepts of effective design. The learning methods that must be practiced are in the form of theory, practice, and design projects. Students are given in-depth knowledge of graphic design software such as Adobe Photoshop, Illustrator, and InDesign. The results of this training are expected to improve students' skills in mastering graphic design science and open up career opportunities in the creative industry.